Estudio de tiempos y movimientos para mejorar el proceso en el transporte de muestras del horno eléctrico al laboratorio por parte de los trabajadores de la empresa acería del ecuador C.A. Adelca - Villegas Guanoluisa, Klever Fabian (2013)
This research was conducted at Acería del Ecuador C. A. ADELCA Company, located in the parish of Aloag, a company dedicated to the recycling of scrap metal and steel production of materials for construction. The feedstock for these processes is the metal scrap. Through the need for better production in less time it has been necessary carry out a study to determine the flaws to be found in the process of transporting steel samples to the laboratory electric oven in the smelter area. So it was important to make an time and motion analysis in this section of the plant, for the purpose of determining the percentage of efficiency in the various activities that are within the process, more efficient working methods, and the approach of a time and standardized activities for the execution of some tasks requiring optimal operating time. Therefore was important to make a time and movement analysis, in order to determine the percentage of efficiency in the various activities that are part of the process, more efficient working methods, and the approach of a standardized time and activities for the execution of some tasks requiring optimal operating time. Finally in the third chapter propose alternatives to standardize activities, readjust the route by which operators are directed transport when samples with this we can optimize production and lower metal billet tasks and reduce operating times, thereby giving effect to the mission and vision of the company